Ultra-long silver nanowires induced mitotic abnormalities and cytokinetic failure in A549 cells. Issue 4 (21st April 2019) - Wang, Fengbang; Chen, Ying; Wang, Yuanyuan; Yin, Yongguang; Qu, Guangbo; Song, Maoyong; Wang, Hailin
Abstract: Asbestos fiber has been associated with mesothelioma and lung cancer. However, the carcinogenic risks of other fiber nanomaterials with morphological similarities to asbestos have not been fully studied. Ultra-long silver nanowires (AgNWs) are increasingly used fiber-shaped nanomaterials with a high aspect ratio, but very few studies have investigated their health risks. Here, proliferation abnormalities of lung epithelial cells induced by ultra-long AgNWs were investigated. Ultra-long AgNW treatment induced dose- and diameter-dependent increase in the ratio of multinucleated cells. Further, proteins involved in mitosis and cytokinesis, including Aurora A, p-Histone 3 (ser10), RhoA, p-MLC, and myosin IIb, were significantly upregulated after an ultra-long AgNW treatment, leading to mitotic abnormalities and cytokinetic failure. Meanwhile, exposure to ultra-long AgNWs induced cell cycle arrest. Interestingly, a series of experiments demonstrated that ROS generation and Ag + release were not responsible for the multinucleation induced by ultra-long AgNWs, but ultra-long AgNWs in the intercellular bridge might obstruct the contractile ring and inhibit abscission of the cytokinetic furrow by direct physical contact. Altogether, our findings indicate that ultra-long AgNWs can induce chromosomal instability, which has important consequences for the safety of ultra-long AgNWs to human health.